2018
DOI: 10.11591/ijece.v8i4.pp2014-2020
|View full text |Cite
|
Sign up to set email alerts
|

Nanometric Modelization of Gas Structure, Multidimensional using COMSOL Software

Abstract: In structures with GaAs, which are the structures most used, because of their physical and electronic proprieties, nevertheless seems a compromise between the increase of doping and reduced mobility. The use of quantum hetero structures can overcome this limitation by creating a 2D carrier gas. Using the COMSOL software this work present three models: the first model computes the electronic states for the heterojunction AlGaAs/GaAs in 1D dimension, the second model computes the electronic states for the hetero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The fabrication process and the characterization of LCP pressure sensing unit are described in [20]. LCP has high mechanical strength, low dielectric constant and various chemical resistance [22,23]. It is suitable for packaging the data transmission and power unit.…”
Section: Methodology 21 Wireless Lcp-based Icp Sensor Design Overviewmentioning
confidence: 99%
“…The fabrication process and the characterization of LCP pressure sensing unit are described in [20]. LCP has high mechanical strength, low dielectric constant and various chemical resistance [22,23]. It is suitable for packaging the data transmission and power unit.…”
Section: Methodology 21 Wireless Lcp-based Icp Sensor Design Overviewmentioning
confidence: 99%
“…The conclusions of the previous study suggested that the sensitivity of the device can be improved by decreasing the thickness of sensing membrane, the variation of sensing membrane thickness is therefore varied to determine the appropriate thickness to provide a higher sensitivity. Modeling and simulation are useful for micro [17] and nano-scale electronic design [18]. A 3D model of the LCP pressure sensor is built using COMSOL Multiphysics (v4.3).…”
Section: Methodsmentioning
confidence: 99%
“…The user defines his couplings or selects the predefined interfaces. The different steps of the modeling process -defining the geometry, the material properties, the mesh, choosing the physics, solving and displaying the results -are integrated into a single interface [16,17].…”
Section: Introductionmentioning
confidence: 99%